The Application of E-module Using Problem Based Learning To Increase Higher Order Thinking Skill And Decrease Misconception In Ecosystem of The Tenth Grade Students of Science 1 Class of Karanganyar 2 State Senior High School In Academic Year 2014-2015 - Dyah Ayu Kaniraras; Puguh Karyanto; Nurmiyati Nurmiyati; Lilis Kusumawati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The purpose of the study is to increase a high order thinking skill and decrease a misconception of the tenth grade students of science 1 class, in Karanganyar 2 state Senior High School through the application of E-module using Problem-Based Learning. This study was a classroom action research, which consisted of two cycles. Each cycle consisted of four stages that were planning, action, observation, and reflection. The subjects of this research were 13 male and 27 female students of the tenth grade students of science 1 in Karanganyar 2 State Senior High School. The validity of the data used triangulation data technique. The methods of data collection comprised test, observation and interview. Data was analyzed descriptively. The result of the study shows an increase of higher order thinking skill. An increase of 35,63% was found in analysis aspect, 30,39% in evaluation aspect, 52,30% in creating aspect, whereas ecology misconception decreases in population concept about 41,94%, 35,63% in community concept, 32,69% in food chain and food web, and a decrese of 35,45% in ecology concept in science, environment, technology & society (SETS) context. The result shows that the application of E-module using Problem-based learning may increase the higher order thinking skill and decrease the misconception.Keywords: E-module using PBL, misconception, high order thinking skill